Evaluation of the demeaning face of COVID-19 on labour relations: a new challenge for Kenya’s burgeoning democracy - Junior, Ratemo Tom (Italian Labour Law e-Journal, 2020)
On March 11th 2020, the World Health Organization was forced to declare the novel coronavirus disease a global pandemic after a surge in reported cases of the disease outside China. The disease has adversely affected, inter alia, the economy and healthcare system in several countries including Kenya. To eradicate the pandemic, the Kenyan Government introduced numerous measures designed to control the infection rate which, inter alia, included closing of non-essential businesses and learning centers, restriction of people movements between 7.00pm and 5.00am and implementation of social distancing rules. These measures have compelled several public and private business entities to either shut or scale down their level of operations in order to remain afloat amid the pandemic. The existing Kenyan labour laws neither incorporate provisions on crisis response nor address the issue of employee safety while working from home. This article therefore seeks to delineate the legal implications of the disease on labour relations in Kenya. Besides, it evaluates effectiveness of the existing labour laws in safeguarding employers and employees’ rights to i.e., health, safety, leave and termination amid the pandemic. It will finally propose measures to be undertaken to fix the loopholes in such laws, if any